Current Clinical Guidelines for the Management of Patients with Glycogen Storage Disease - Natalia A. Averkina; Madlena E. Bagaeva; Aleksander A. Baranov; Nato D. Vashakmadze; Elena A. Vishneva; Olga S. Gundobina; Nataliya V. Zhurkova; Elena V. Kaitukova; Elena V. Komarova; Tea V. Margieva; Leyla S. Namazova-Baranova; Valeria P. Novikova; et al. (Педиатрическая фармакология)
Glycogen storage disease refers to hereditary pathologies of carbohydrate metabolism, its cause is mutations of various genes encoding enzymes responsible for the synthesis and breakdown of glycogen. Due to enzyme defects, excessive glycogen deposition occurs in cells of various tissues, mainly in the liver and muscles. The authors present modern epidemiological data and features of the etiopathogenesis of glycogen storage disease, and give clinical characteristics of various types of this nosology. In accordance with the developed clinical guidelines, information is provided on laboratory, instrumental and morphological signs of glycogen storage disease in children, as well as on methods of treatment of glycogen storage disease. Due to the variety of clinical forms of glycogenosis, the article provides up-to-date information on three types of pathology that occur with predominant liver damage.